Differences in eating behaviors, dietary intake and body weight status between male and fermale Malaysian University students. - Gan, W.Y.; Mohd Taib, Mohd Nasir; Mohd Shariff, Zalilah; Abu Saad, Hazizi (Nutrition Society of Malaysia, 2011)
University students are potentially important targets for the promotion of healthy lifestyles as this may reduce the risks of lifestyle-related disorders later in life. This cross-sectional study examined differences in eating behaviours, dietary intake, weight status, and body composition between male and female university students. A total of 584 students (59.4% females and 40.6% males) aged 20.6 +/- 1.4 years from four Malaysian universities in the Klang Valley participated in this study. Participants completed the Eating Behaviours Questionnaire and two-day 24-hour dietary recall. Body weight, height, waist circumference and percentage of body fat were measured. About 14.3% of males and 22.4% of females were underweight, while 14.0% of males and 12.3% of females were overweight and obese. A majority of the participants (73.8% males and 74.6% females) skipped at least one meal daily in the past seven days. Breakfast was the most frequently skipped meal. Both males and females frequently snacked during morning tea time. Fruits and biscuits were the most frequently consumed snack items. More than half of the participants did not meet the Malaysian Recommended Nutrient Intake (RNI) for energy, vitamin C, thiamine, riboflavin, niacin, iron (females only), and calcium. Significantly more males than females achieved the RNI levels for energy, protein and iron intakes. This study highlights the presence of unhealthy eating behaviours, inadequate nutrient intake, and a high prevalence of underweight among university students. Energy and nutrient intakes differed between the sexes. Therefore, promoting healthy eating among young adults is crucial to achieve a healthy nutritional status.